Molecular mechanism of the actin-associated protein hip1r on malignant 8-cell migration - Keng, Wong Kah (Pusat Pengajian Kesihatan, 2015)
Cancer research at Universiti Sains Malaysia (USM) has been increasingly active in recent years. Many young researchers who recently started their service in USM work on cancer. The inaugural Next Generation Researchers Cancer Symposium organized by the Centre for Research Initiative - Clinical and Health Sciences (CRI-CHS) is thus initiated to bring together these young researchers with diverse expertise from various faculties in USM, to share and discuss various aspects of cancer research and new research tools. The meeting is aimed to provide an active platform for communication, knowledge-sharing and collaboration among these young researchers and also to initiate research interactions with senior academic members. a. To provide a platform for meaningful and active interactions between researchers working on cancer b. To address on types of research funding available c. To discuss the role and expectations of a researcher in an academic institution.